(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Pazyura N. V. Corporate human resource development as a factor of personal improvement. In the article different approaches to the definition of human resource development are considered. The nature and aim of corporate human resource development are clarified on this basis. The author has found peculiarities in its functioning and specified the influence the theoretic views on the practice of human development that is considered as essential part of personal improvement.